2004
DOI: 10.1523/jneurosci.1470-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Akt-1 Expression Level Regulates CNS Precursors

Abstract: Although most cells in the embryonic mouse cortex express the serine-threonine kinase Akt-1, a small population of progenitors expresses Akt-1 protein at a higher level. To determine the functional significance of this difference, we used a retrovirus to increase Akt-1 expression in cortical progenitors. Increased Akt expression enhanced Akt activation after growth factor stimulation of progenitors. In vivo, it promoted retention in progenitor layers, the ventricular zone and subventricular zone. In vitro, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
94
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 60 publications
12
94
0
Order By: Relevance
“…It is becoming recognized that the absolute level of a specific transcription factor is an important component of the mechanism of lineage specific regulation (Kulessa et al 1995;DeKoter and Singh 2000;Motohashi et al 2000Motohashi et al , 2004Emambokus et al 2003). Moreover, it has been proposed that neural progenitor cell heterogeneity is triggered in part through a gene-dosage effect (Marquardt and Gruss 2002;Sinor and Lillien 2004).…”
Section: Eye Morphogenesis In Sox2 Hypomorphic Micementioning
confidence: 99%
“…It is becoming recognized that the absolute level of a specific transcription factor is an important component of the mechanism of lineage specific regulation (Kulessa et al 1995;DeKoter and Singh 2000;Motohashi et al 2000Motohashi et al , 2004Emambokus et al 2003). Moreover, it has been proposed that neural progenitor cell heterogeneity is triggered in part through a gene-dosage effect (Marquardt and Gruss 2002;Sinor and Lillien 2004).…”
Section: Eye Morphogenesis In Sox2 Hypomorphic Micementioning
confidence: 99%
“…This signaling module plays a pivotal role in the regulation of cell survival, proliferation, and size in many systems (25)(26)(27)(28). In fact, a number of studies has suggested the roles of the PI3K-Akt pathway in NPC proliferation and/or differentiation (29)(30)(31)(32)(33). However, even though PDK1 and all 3 members of the Akt family are expressed in the developing CNS, genetic evidence for their importance in CNS development is lacking.…”
mentioning
confidence: 99%
“…Increased Akt-1 expression in cortical progenitors enhances proliferation and survival in vitro. This process depends on mTOR activity, and rapamycin has been shown to eliminate the Akt-1-mediated increase in stem cells and to reduce proliferation (Sinor and Lillien, 2004). Moreover, Notch ligand can expand stem cells both in vitro and in vivo.…”
Section: Review Of Zeng Et Almentioning
confidence: 99%